Pengaruh Jenis Karagenan terhadap Karakteristik Fisik Gel Anti Jerawat. - Yuyun Nailufa; Yuli Ainun Najih; Dita Nurlita Rakhma (Jurnal Health Sains, 2021)
Acne (acne vulgaris) is a disease characterized by inflammation of the skin that can cause skin infections. The purpose of this study was to find out the effect of karagenan types (kappa, iota and lamda) on the physical characteristics of anti-acne gels. The research method used is qualitative method. In this study conducted the manufacture of gel preparations with gelling agent karagenan. The types of karagenan used are kappa, iota and lamda.  The concentration used is the same as 1%. Based on the test results obtained that the gel that has the best characteristics that are easy to flatten, clear, soft and good viscosity means not too diluted and not too viscosic is formula 2 with gelling agent iota karagenan. The results of formula 1 with gelling agent kappa karagenan obtained a gel that is stiff, less clear and difficult to flatten. While in formula 3 with gelling agent lamda karagenan obtained a clear but diluted gel. Based on the results of the stability test of the three formulas are stable with the centrifuge method with a speed of 3000 rpm for 5 hours.